Persamaan Hak bagi Tersangka atau Terdakwa untuk Memperoleh Bantuan Hukum dalam Kitab Undang- Undang Hukum Acara Pidana (KUHAP) - Gatot Triyanto (Fakultas Hukum Universitas Islam Jember, 2018)
For a suspect or defendant who commits a criminal act threatened with a sentence under five years, the right to legal assistance has been recognized but is not included in the mandatory rights. This means that the process of examining and investigating suspects or defendants can proceed without being accompanied by an advocate and there are no legal consequences for the cancellation of the investigation report or indictment. Therefore the legal assistance stipulated in the Criminal Procedure Code is not sufficient for the poor who need legal aid services. Legal assistance is closer to those who are able to provide or pay compensation services to people who work as advocates. Thus, legal assistance is regulated in the Criminal Procedure Code. not reflecting or realizing equal rights and treatment before the law for access to justice. Keywords: Rights, Suspects / Defendants, Legal Aid